Lac repressor with the helix-turn-helix motif of lambda cro binds to lac operator. - Kolkhof, P (1992)
Lac repressor, lambda cro protein and their operator complexes are structurally, biochemically and genetically well analysed. Both proteins contain a helix-turn-helix (HTH) motif which they use to bind specifically to their operators. The DNA sequences 5'-GTGA-3' and 5'-TCAC-3' recognized in palindromic lac operator are the same as in lambda operator but their order is inverted form head to head to tail to tail. Different modes of aggregation of the monomers of the two proteins determine the different arrangements of the HTH motifs. Here we show that the HTH motif of lambda cro protein can replace the HTH motif of Lac repressor without changing its specificity. Such hybrid Lac repressor is unstable. It binds in vitro more weakly than Lac repressor but with the same specificity to ideal lac operator. It does not bind to consensus lambda operator.